Addressing barriers to post-graduate research training in low resource settings: an innovative approach in an institution of higher learning in Kenya - Mwangi, Eunice Muthoni; Iseme-Ondiek, Rosebella Alungata; Riang'a, Roselyter Monchari; Orwa, James; Njenga, Kennedy W.; Ngugi, Anthony K. (Frontiers in Medicine, 2024)
Background Numerous barriers hinder health research training in Post-Graduate Medical Education Programs, especially in developing countries. Research training is pivotal for medical residency, providing essential knowledge and skills for dissertation completion, fostering evidence-based medical practice, and nurturing future independent clinical researchers. A holistic approach to research education is imperative to surmount these barriers. We describe here a dissertation-centric research curriculum, delivered longitudinally, an innovative strategy undertaken by Aga Khan University's Medical College in East Africa (AKU-MCEA) to deliver postgraduate research. Methods A review of AKU-MCEA post-graduate research methods curriculum was conducted based on implementing Departments' experience, institutional policies, and residency program output. Program implementation The Master of Medicine program requires a well-executed dissertation for graduation. Residents undergo structured research training across four modules, with interactive sessions and workshops supporting their research milestones. Protected time allows residents to develop and report on their dissertation work. Faculty receive specialized training in dissertation supervision to ensure residents benefit from expert guidance in producing high-quality research. Outcomes This approach achieves a dissertation completion and graduation rate of 98–100%. Notably, 68.5% (n = 126) of those who graduated in 2013–2023 have published two or more papers (i.e., range 2–36) in their current portfolio, demonstrating a commitment to ongoing research endeavors even after graduation. Residents' research covers diverse themes and is disseminated through departmental presentations, university-wide Faculty Academic Rounds, peer-reviewed journals, conferences, and the Annual Early Career Researchers symposium. Lessons learnt A comprehensive approach featuring a structured research curriculum, longitudinal delivery with predetermined milestones, dedicated supervision, financial and resource support, protected research time, ongoing faculty development in dissertation supervision, and clear institutional research policies accelerates dissertation completion and enhances effective research dissemination.